Marigold-globe amaranth sequential cropping in coconut plantations of coastal humid tropics - A. Abdul Haris, K. Nihad, V. Krishnakumar (Journal of Plantation Crops, 2017)
Marigold (Tagetus erecta) and globe amaranth (Gomphrena globosa) are two potential commercial loose flower crops with high market demand during festive seasons. Climate of coastal humid tropics is suitable for growing marigold and globe amaranth during October to April and May to September, respectively, where the flowering season coincides with the peak demand fetching higher market price. A field study was conducted in two consecutive years at ICAR-CPCRI, Regional Station, Kayamkulam during 2010-12 for standardising the nutrient management practice for marigold-globe amaranth sequential cropping under coconut based farming system in coastal humid tropics. The treatments were fixed based on nitrogen equivalent basis. In the study, marigold alone was supplied with nutrition and globe amaranth was raised with the available field residues of first crop. Intercropping marigold was supplied with basal dose of vermicompost (16.8 kg N ha-1) followed by 16.8:18:18 kg NPK ha-1 at 15 days after transplanting and vermicompost extract (1:10), to meet 4.4 kg N ha-1 equivalent, at 30 days and 45 days after transplanting resulted in fresh flower yield of 2 t ha-1 of coconut plantations. The plant height, number of primary and secondary branches, number of flowers plant-1, flower yield, and flower carotenoid content of marigold were also higher in this treatment. The growth or yield of globe amaranth did not differ among the treatments, and on an average it produced fresh flower yield of 1.9 t ha-1 from the interspaces of coconut. This study on sequential cropping of flower crops revealed that substituting 50 per cent inorganic nitrogen requirement of marigold with vermicompost enhances its growth performance and also provides adequate nutrition for raising globe amaranth during its vegetative phase (upto 60 days after transplanting) resulting in a B:C ratio of 2.8.